Silk Roads Routes. Sustainable Tourism after COVID-19 - TECZKE, Maciej; KALIYEVA, Talant; SEMBIYEVA, Lyazzat; ZHAGYPAROVA, Aida; ZHOLAMANOVA, Makpal; ZHUSSUPOVA, Aigerim (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).24, 2022)
Since ancient times, people have traveled and exchanged goods, technology and ideas with neighboring settlements. The vast Eurasian continent has traditionally been a crossroads of trade routes, which helped create the increasingly famous Silk Road. Sea routes were created connecting East and West by water, which were mainly used for the trade in spices, which gave rise to the "spice route". Numerous road networks helped not only in the transportation of goods and luxury goods, but also in the transfer of knowledge, ideas, culture and beliefs, and had a great influence on the history and development of the Eurasian civilization, as well as the development of tourism and its various directions. This research paper intends to provide an analysis covering countries near and far abroad in the field of tourism and travel, tourism policy with indicators of sustainability and comparison of indicators of sustainable consumption and production patterns. Summarizing the results obtained, we concluded about the potential areas for improvement in the tourism industry and proposed a new set of recommendations for their evaluation.